Human Induced Pluripotent Stem Cells Differentiate Into Functional Mesenchymal Stem Cells and Repair Bone Defects. (11th July 2016) - Sheyn, Dmitriy; Ben-David, Shiran; Shapiro, Galina; De Mel, Sandra; Bez, Maxim; Ornelas, Loren; Sahabian, Anais; Sareen, Dhruv; Da, Xiaoyu; Pelled, Gadi; Tawackoli, Wafa; Liu, Zhenqiu; et al.
Abstract : Using short-term exposure of embryoid bodies to transforming growth factor- β, the authors directed induced pluripotent stem cells (iPSCs) toward mesenchymal stem cell (MSC) differentiation. Two types of iPSC-derived MSCs were identified: early (aiMSCs) and late (tiMSCs) outgrowing cells. Both types differentiated in vitro in response to osteogenic or adipogenic supplements; aiMSCs demonstrated higher osteogenic potential than tiMSCs. Upon orthotopic injection into radial defects, both types regenerated bone and contributed to defect repair. Abstract: Mesenchymal stem cells (MSCs) are currently the most established cells for skeletal tissue engineering and regeneration; however, their availability and capability of self-renewal are limited. Recent discoveries of somatic cell reprogramming may be used to overcome these challenges. We hypothesized that induced pluripotent stem cells (iPSCs) that were differentiated into MSCs could be used for bone regeneration. Short-term exposure of embryoid bodies to transforming growth factor- β was used to direct iPSCs toward MSC differentiation. During this process, two types of iPSC-derived MSCs (iMSCs) were identified: early (aiMSCs) and late (tiMSCs) outgrowing cells. The transition of iPSCs toward MSCs was documented using MSC marker flow cytometry. Both types of iMSCs differentiated in vitro in response to osteogenic or adipogenic supplements. The results of quantitative assays showed that both cell types retained their multidifferentiation potential, although aiMSCs demonstrated higher osteogenic potential than tiMSCs and bone marrow-derived MSCs (BM-MSCs). Ectopic injections of BMP6 -overexpressing tiMSCs produced no or limited bone formation, whereas similar injections of BMP6- overexpressing aiMSCs resulted in substantial bone formation. Upon orthotopic injection into radial defects, all three cell types regenerated bone and contributed to defect repair. In conclusion, MSCs can be derived from iPSCs and exhibit self-renewal without tumorigenic ability. Compared with BM-MSCs, aiMSCs acquire more of a stem cell phenotype, whereas tiMSCs acquire more of a differentiated osteoblast phenotype, which aids bone regeneration but does not allow the cells to induce ectopic bone formation (even when triggered by bone morphogenetic proteins), unless in an orthotopic site of bone fracture. Significance: Mesenchymal stem cells (MSCs) are currently the most established cells for skeletal tissue engineering and regeneration of various skeletal conditions; however, availability of autologous MSCs is very limited. This study demonstrates a new method to differentiate human fibroblast-derived induced pluripotent stem cells (iPSCs) to cells with MSC properties, which we comprehensively characterized including differentiation potential and transcriptomic analysis. We showed that these iPS-derived MSCs are able to regenerate nonunion bone defects in mice more efficiently than bone marrow-derived human MSCs when overexpressing BMP6 using a nonviral transfection method.